Analisis Penetapan Harga Jasa Servis Sepeda Di Bengkel Ma’had Al-Zaytun Dalam Perspektif Prinsip Keadilan Ekonomi Islam - Ilmi, Anida Maysah; Prawoto, Imam; Maulana, Rizal (Institut Agama Islam Sumatera Barat Pariaman, 2025)
This study analyzes the pricing mechanism for bicycle repair services at Ma’had Al-Zaytun Workshop based on the principles of Islamic economic justice. Employing a qualitative method with a field research approach, data were collected through interviews, observations, and documentation. The findings indicate that pricing is determined by considering the cost of raw materials, spare parts, operational expenses, repair services, and market research. Although prices are mutually agreed upon, the absence of a clear wage standard may lead to potential injustice. From the perspective of Islamic economic justice, this pricing mechanism does not fully reflect balance and transparency. Therefore, a more structured pricing policy is needed to ensure fair transactions for all parties.